Integrated membrane operations in the food production - Cassano, Alfredo; Charcosset, Catherine; Conidi, Carmela; Crespo, João G.; Cuperus, F. Petrus; De, Sirshendu; Drioli, E.; Franken, A. C. M. (Ton); Gani, R.; Gésan-Guiziou, Genevieve; Giorno, Lidietta; Jiao, Bining; et al. (Walter de Gruyter GmbH & Co., KG, 2014)
Membranes are the most effective separation processes with practically unlimited selectivity of separation and seem to be very promising and profitable in designing of the innovative Clean Technologies, which will become inevitably necessary on the long run. An introduction to integrated membrane operations is followd by applications in the several industries of the food sector.